Essays on corruption and responsibility - Verbel Bustamante, Yuliet (2023)
This thesis contributes to the investigation of corruption and, in particular, to the understanding of responsibility as a driver of corrupt decisions. I write three chapters investigating various ways responsibility shapes decisions and perceptions of corruption. I start by providing a general introduction that gives an overview of the main topic of the thesis and the three chapters contained in it. I give a summary of each chapter below.